The empirical evaluation of monetary policy shock in dynamic stochastic general equilibrium model with financial frictions: Case of Croatia. (19th February 2018) - Palić, Irena
Large body of empirical literature points to the tight integration of financial and credit markets with real economic activity as well as the need for inclusion of financial frictions into macroeconomic modelling. After the recent mortgage loan crisis which spilled over into the global financial crisis, the assessment of relationship of monetary policy and house prices gained in importance. The aim of this article is to test the compliance of monetary policy shock in calibrated dynamic stochastic general equilibrium (DSGE) model which includes financial frictions with the empirical impact of monetary policy shock in Croatia estimated using vector autoregression (VAR) model. After the DSGE model is calibrated, the VAR model is estimated for Croatia. The comparative analysis of impulse response functions of DSGE and VAR model is conducted. In both models, monetary policy shock has positive initial impact on interest rate and negative initial impact on house prices and output gap. Results indicate that empirical impact of the monetary policy shock adequately reflects the impact of monetary shock in DSGE model with financial frictions.